2019
DOI: 10.1080/08897077.2019.1616349
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ Attitudes toward Dispensing Naloxone and Medications for Opioid Use Disorder: A Scoping Review of the Literature

Abstract: Background Pharmacists are on the frontline caring for patients at risk of an opioid overdose and for patients with an opioid use disorder (OUD). Dispensing naloxone and medications for OUD and counseling patients about these medications are ways pharmacists can provide care. Key to pharmacists’ involvement is their willingness to take on these practice responsibilities. Methods The purpose of this scoping review is to identify, evaluate, and summarize published literature describing pharmacists’ attitudes tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…This study is the first to look at these pharmacists outside of a medical office and report what they know and think regarding MAT for OUD, especially for methadone and naltrexone. 20 These findings demonstrate an opportunity for education in specific content areas. Most respondents demonstrated an understanding regarding MAT access for OUD.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This study is the first to look at these pharmacists outside of a medical office and report what they know and think regarding MAT for OUD, especially for methadone and naltrexone. 20 These findings demonstrate an opportunity for education in specific content areas. Most respondents demonstrated an understanding regarding MAT access for OUD.…”
Section: Discussionmentioning
confidence: 89%
“…Existing U.S.-based research has demonstrated success in primary careebased MAT with documented treatment access improvement for SUDs, but potential pharmacist roles have not been well studied. 18,19 Muzyk et al 20 conducted a literature review for U.S.-based research that reported pharmacists' attitudes toward OUD medications and identified 2 studies evaluating buprenorphine products. 20 In the first study, most pharmacists and technicians involved in an office-based opioid dependence treatment program using buprenorphine-naloxone expressed positive attitudes and perceptions regarding patients treated in that setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Despite efforts to increase naloxone access nationwide, pharmacist-initiated dispensing remains low. 7,8 Limited naloxone dispensing suggests the presence of barriers for pharmacists, and studies assessing these barriers are sparse. Carpenter et al, 7 in a study of community pharmacists in North Carolina, examined factors related to how frequently pharmacists offered and dispensed naloxone.…”
Section: Introductionmentioning
confidence: 99%